(3GdEYdGe GdYQHj Edi GdbQf GdhGMO h GdYTQjf (B/s - (3LGf LHQGf, cQes ((3HjQhJ(B- (3dHfGf (B:s (3OGQ GdLjd ,s, 1999)
(3Cjf CYdGefG ef chSehS GdGJUGdGJ GdHGgQ? Efg aj GdZGdH Pdc GdGYdQGHj GdWGdY ef bUU GdLGMX h bO KbdJ cJag HGdUMhf GddGbWI h Sef MUQg HGdMhGSjH h TGTGJ GdJdaRjhf h JOfOdJ ef Mbhjg GdeWGHY GdEdcJQhfjI h JTfTdJ bOeGA HaFQGf GdGfJQfjJ h ghGFjGJ GdShGJd MGKG GdNWi fMh QheG Gh HGQjS GhdfOf Gh GWdfWG dMLR ebYO aj GMO fhGOj GdJcfhdhLjG h Ydhe GdEJUGd (B.... (3CeG GadjGJfG ef GdPjf jRjOhf GdNQhL ef GdUhQI djchfhG ge GUMGH GdQRb h GdUfGYI h GdJUhjQ age GdYdGeI GdaGQbI aj HOGjI GdbQf GdLOjO h ge GddPjf SjNdYhf Yf GdGYQGHj eTJQjGJg h ebJfjGJg djLYdhG efg UGfY MGVQ h eSJbHd h QGFO JcfhdhLjG eJbOeI JNOe GdEfSGf GdYQHj h GdEfSGf aj GdYGde GdhGSYs
Keywords: (3GdEYdGe GdYQHjs